2016
DOI: 10.5455/medarh.2016.70.182-185
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Neonates with Seizures; a Prospective Cohort Study

Abstract: Objective:The aim of this study was to analyze prognostic indicators for mortality in neonates with seizures in a level III Neonatal Intensive Care Unit (NICU).Patients and methods:A cohort of 100 neonates with clinically manifested seizures hospitalized in the NICU during 4 years period was prospectively monitored for the first year of life. The cohort consisted of 33 preterm and 67 full-term babies with 60 male and 40 female infants.Results:The mortality rate in the first year of life of infants with seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Similar to previous reports, HIE followed by ICH was the most common reason for neonatal seizures. 12,20,21 Although the overall incidence of neonatal seizures was similar to a rate of two to five per 1,000 live births reported in the literature, [5][6][7][8][9] the 30% mortality rate found in the current study is almost double the rate compared with that reported by others. 20,[22][23][24] This may be explained by the characteristics of the study population and the high rate of consanguinity found in the current study compared with other reports.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous reports, HIE followed by ICH was the most common reason for neonatal seizures. 12,20,21 Although the overall incidence of neonatal seizures was similar to a rate of two to five per 1,000 live births reported in the literature, [5][6][7][8][9] the 30% mortality rate found in the current study is almost double the rate compared with that reported by others. 20,[22][23][24] This may be explained by the characteristics of the study population and the high rate of consanguinity found in the current study compared with other reports.…”
Section: Discussionsupporting
confidence: 85%
“…3,10 Mortality among neonates with seizures may reach 20% in the first year of life, particularly when accompanied with prematurity, low birthweight (LBW), low Apgar score, severe neonatal infection, severe hypoxic-ischemic encephalopathy (HIE), brain malformations, grade 3 or 4 intraventricular hemorrhage (IVH), and intracranial hemorrhage (ICH). 11,12 It is essential to determine etiology to effectively treat the underlying cause and to offer a reasonable prognosis when counseling parents. 3 Our institution is the most prominent health care providing institution in the northeast of Israel.…”
Section: Introductionmentioning
confidence: 99%
“…Global cerebral hypoxiaischemia is the most common etiology of neonatal seizures, followed by intracranial bleed, hypoglycemia, septicemia, hypocalcemia, BE, CNS malformations. 22 Seizure etiology, early onset of seizures, prolonged, repetitive and the need for multiple anticonvulsants to control seizure activity are always associated with an increased mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Normally, seizures are indicative of an underlying dysfunction in the brain. Early life seizures are widely described as a neurological emergency due to a mortality rate as high as 23% and are well documented to cause later life comorbidities such as postnatal epilepsy and global neurodevelopmental delay [3,15]. A seizure is presented when the physiology of the brain abnormally favours excitatory neurotransmission, i.e., promotion of glutamatergic and disinhibition of γ-aminobutyric acid (GABA)ergic transmission.…”
Section: Neonatal Seizuresmentioning
confidence: 99%
“…Presentation of neonatal seizures is most commonly symptomatic of an underlying aetiology rather than idiopathic. Many risk factors associated with neonatal seizures are related to a metabolic imbalance during pregnancy or immediately postdelivery, including perinatal infection, hypoglycaemia and intracranial haemorrhage [4,15,27]. Moreover, rare cases of an inborn genetic component of neonatal seizures exist, with the majority altering metabolic pathways, including KCNQ2 mutations, infantile hypophosphatasia (mutations in the tissue nonspecific alkaline phosphatase (TNAP)) and propionic acidaemia (deficiency of propionyl-CoA carboxylase) [27].…”
Section: Aetiologies Of Neonatal Seizuresmentioning
confidence: 99%